2023
DOI: 10.1021/acs.jced.3c00364
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Measurement and Thermodynamic Properties of Fluorene in 14 Pure Solvents at Temperatures from 278.15 to 318.15 K

Mengxin Sun,
Yuntian Xiao,
Yixin Zhou
et al.

Abstract: In this study, the solubility data of fluorene in 14 pure organic solvents (methanol, ethanol, n-propanol, isopropanol, ethyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, propanone, acetonitrile, and tetrahydrofuran) from 278.15 to 318.15 K were measured using a gravimetric method at atmospheric pressure. Four thermodynamic models, including the modified Apelblat model, λh model, van’t Hoff model, and NRTL model, were employed to correlate solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The PXRD patterns of the raw material of fluorene and the solid residues in the six binary solvents are presented in Figure , which corresponds to the report in the literature . It can be observed that the characteristic peaks of fluorene in the selected solvents had no change compared to that of the raw material, which indicates that no polymorphic transformation of fluorene appeared in the experimental process. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PXRD patterns of the raw material of fluorene and the solid residues in the six binary solvents are presented in Figure , which corresponds to the report in the literature . It can be observed that the characteristic peaks of fluorene in the selected solvents had no change compared to that of the raw material, which indicates that no polymorphic transformation of fluorene appeared in the experimental process. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…The DSC curve of fluorene is shown in Figure . The result indicates that the melting point ( T m ) of fluorene is 387.49 K and the melting enthalpy is ( Δ fus H ) = 17.103 kJ/mol, which is compared to the reported documentation ( T m = 387.92 K and Δ fus H = 16.948 kJ/mol in ref ; T m = 387.943 K and Δ fus H = 19.58 kJ/mol in ref ). Standard uncertainties for the melting point ( T m ) and melting enthalpy ( Δ fus H) are u ( T m ) = 0.5 K and u ( Δ fus H ) = 0.5 kJ/mol, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubility of 4-MBA in 14 distinct solvents was ascertained through the application of the gravimetric method within the temperature spectrum of 283.15–328.15 K. Approximately, 30 mL of the organic solvent was placed in a 50 mL conical flask. Subsequently, an excess of 4-MBA was introduced to ensure the avoidance of complete solid solute dissolution.…”
Section: Methodsmentioning
confidence: 99%
“…The Modified Apelblat equation is a semiempirical equation that is derived from the Clausius–Clapeyron equation. Due to its simple expression, it is extensively employed in the correlation of solid–liquid equilibrium data. The Modified Apelblat equation can be represented as follows ln nobreak0em0.25em⁡ x = A + B T + C ln nobreak0em0.25em⁡ T where x signifies the mole fraction of 4-MBA at the absolute temperature “ T ” in Kelvin during the experiment. The equation is defined by three empirical constants, namely, A, B, and C. Parameters A and B are indicative of the nonideality within the solution, accounting for variations in activity coefficients, while parameter C characterizes the influence of temperature on the enthalpy of fusion.…”
Section: Methodsmentioning
confidence: 99%